2016
DOI: 10.3899/jrheum.151389
|View full text |Cite
|
Sign up to set email alerts
|

Comparable Efficacy of Abatacept Used as First-line or Second-line Biological Agent for Severe Juvenile Idiopathic Arthritis-related Uveitis

Abstract: ABA, used as first-line biological treatment or after 1 or more anti-TNF agents, induces a comparable improvement in severe refractory JIA-related uveitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(34 citation statements)
references
References 23 publications
1
31
1
1
Order By: Relevance
“…103 The most recent retrospective case series with 31 patients showed that when abatacept was used as first-line or second-line therapy, >50% of patients had complete remission after 12 months, a comparable result to TNF-α inhibitors. 104 Further studies via well designed prospective randomised controlled trials with larger populations will be required to confirm the findings on these therapies. Table 2 summarises the current recommended dosages, routes of administration, and common adverse events of the biologic agents reviewed in this paper and registered in Australia and New Zealand.…”
Section: Other Targeted Biologic Therapymentioning
confidence: 98%
See 1 more Smart Citation
“…103 The most recent retrospective case series with 31 patients showed that when abatacept was used as first-line or second-line therapy, >50% of patients had complete remission after 12 months, a comparable result to TNF-α inhibitors. 104 Further studies via well designed prospective randomised controlled trials with larger populations will be required to confirm the findings on these therapies. Table 2 summarises the current recommended dosages, routes of administration, and common adverse events of the biologic agents reviewed in this paper and registered in Australia and New Zealand.…”
Section: Other Targeted Biologic Therapymentioning
confidence: 98%
“…Abatacept has been shown to be a valid alternative to TNF‐α inhibitors for the treatment of severe JIA‐related uveitis . The most recent retrospective case series with 31 patients showed that when abatacept was used as first‐line or second‐line therapy, >50% of patients had complete remission after 12 months, a comparable result to TNF‐α inhibitors …”
Section: Other Targeted Biologic Therapymentioning
confidence: 99%
“…Based on the current literature, recommended alternative nonbiologic options are mycophenolate mofetil (40), leflunomide (41), or cyclosporine (42), and recommended alternative biologic options are abatacept (43)(44)(45) or tocilizumab (46,47); however, evidence supporting preference for a specific nonbiologic or biologic DMARD, combination therapies, and timing of initiation beyond methotrexate, adalimumab, and infliximab is currently lacking. Based on the current literature, recommended alternative nonbiologic options are mycophenolate mofetil (40), leflunomide (41), or cyclosporine (42), and recommended alternative biologic options are abatacept (43)(44)(45) or tocilizumab (46,47); however, evidence supporting preference for a specific nonbiologic or biologic DMARD, combination therapies, and timing of initiation beyond methotrexate, adalimumab, and infliximab is currently lacking.…”
Section: Recommendation 15mentioning
confidence: 99%
“…Various clinical studies have investigated the use of abatacept for Th1 mediated diseases such as psoriatic arthritis, rheumatoid arthritis and JIA. Furthermore, abatacept has also shown efficacy in patients with uveitis associated with JIA . Several reports have demonstrated the efficacy of abatacept in cases of uveitis refractory to other anti‐TNF agents .…”
Section: Emerging and Adopted Therapiesmentioning
confidence: 99%
“…Furthermore, abatacept has also shown efficacy in patients with uveitis associated with JIA. [207][208][209] Several reports have demonstrated the efficacy of abatacept in cases of uveitis refractory to other anti-TNF agents. [210][211][212] Further larger clinical trials need to be conducted to understand fully the safety and efficacy profile of abatacept.…”
Section: Abataceptmentioning
confidence: 99%